La lectura di Max Weber dell’ hinduismo e del budismo nella sociología delle religiones (Gesammelte aufsatze zur religionssoziologie). Un esercizio di ammirazione - Piro, Pietro (ENDOXA, 2015)
The text analyzes the reflections of Max Weber in Gesammelte Aufsätze zur Religionssoziologie dedicated to Hinduism and Buddhism. The initial intention was to find the "limits" of Weber. However, after careful reading, Weber’s work demonstrates the ability to "hold over time and at the time" and continues to exert a considerable charisma. The size of the survey Weber is represented by its extraordinary ability to ask radical questions and groped me give you some answers. Answers still valid today and worthy of the greatest interest.